Critical Review of the Implementation of the Making of SOE as a Holding from Anti-Monopoly and Unfair Business Competition Perspective - Huta Disyon; Elisatris Gultom (Jurnal Penelitian Hukum De Jure, 2022)
This study aims to analyze the potential for SOE holdings to violate Law 5/1999. This study was conducted using a normative juridical method because the study was based on library research to obtain secondary data, sourced from primary, secondary, and tertiary legal materials. The specification of the research was descriptive-analytical because the author described the holding of SOE and then analyzed it to see if it has the potential to cause a violation of Law 5/1999. Data analysis using a qualitative juridical method. The results of the study indicated that the process of establishing an SOE holding based on Government Regulation Number 72 of 2016, so far has not been proven to have violated Law 5/1999. However, even though Article 33 of the Constitution of the Republic of Indonesia and Article 51 of Law 5/1999 intend SOE to be able to carry out a monopoly, the establishment of an SOE holding should still be able to guarantee the rights of the public to continue to do business in a healthy manner. The government needs to immediately stipulate regulations regarding governance in holding companies to maintain a competitive, healthy, and non-monopolistic business climate.